(3Yjhf GdCNHGQ ajeG hbY dLGeYg aj GdGbGeI hGdCSaGQs - (3YeQ GdTeGY , YeQ Hf CMeO Hf Ydj GdTeGY GdMdHj, Rjf GdOjf CHh MaU,J (B936 (3g` s
(3ChdgG (B:s
(3GdMeO ddg ebOQ GdSchf hGdMQcGJ s
(3ai BNQ GdfSNI JQLeI ddeDdas
(3jYQa CjVkG HGdahGFO hGdOQQ ajeG hbY dg ai GdSaQ hGdMVQs
(3jYQa CjVkG RHOI GdNHQ ajeG hbY ai GdEbGeI hGdSaQs
(3jYQa CjVkG ef GdZjHI ajeG hbY ai GdEbGeI hGdZjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B41 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B274s
Keywords: (3GdJGQjNs